Measurement of Anaerobic Capacity Based On Fatigue Index for Pencak Silat Athletes on Combat Category - Subekti, Nur; Syaukani, Agam Ahmad; Fatoni, Muhad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: This research aims to investigate anaerobic capacity for pencak silat athletes in combat category based on fatigue index.Methodology: The method used in this study is descriptive quantitative. Fifteen athletes from sport education undergraduate program were recruited in this study. Their background was all from combat category. They were part of varsity team enrolled in university training center and preparing for provincial college sport competition. The data for anaerobic capacity were collected using Runningbased Anaerobic Sprint Test (RAST) with validity level of 0.897 and reliability level of 0.919.Results: The results suggested that in terms of anaerobic capacity level, there are 4 athletes (26.67%) categorized as good, 8 athletes (53.33%) categorized as average, and 3 athletes (20.00%) categorized as poor. Based on the measurement being administered, majority of samples on this study attributed to average level of anaerobic capacity..Applications/Originality/Value: Given that pencak silat is sport in which dominant with anaerobic movement, coaches should prioritize anaerobic training to improve anaerobic capacity which may lead to success in combat.